A most convenient and patient compliance dosage form- Tablet - Rajiv Kumar; Batth, Kiranjeet Kaur; Kaur, Jaspreet; Jaspreet Kaur; Parminder Nain; Dhawan, R.K. (Journal of Biomedical and Pharmaceutical Research, 2020)
Tablet is defined as solid pharmaceutical dosage form containing drug substance generally with suitable diluents and prepared by either compression which is given as a single unit and are known as solid unit dosage form. Tablets remain popular as a dosage form because of the advantages afforded, both to the manufacturer (e.g. simplicity and economy of the preparation, stability, and convenience in packing, shipping and dispensing) and the patient. The excipients include diluents, Binders and adhesives, disintegrates, etc. Tablets vary in shape and differ greatly in size and weight depending on the amount of the medicinal substance. The ingredients must be granulated prior to compression to assure an even distribution of the active compound in the final tablet. There are two basic techniques which can be used to granulate powders for compressions into a tablet are wet granulation and dry granulation. In this review article tablet manufacturing and evaluation have been discussed. Keywords- Tablet, Granulation, Picking and sticking, Dissolution test, weight variation